1991
DOI: 10.1021/j100155a067
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of adsorbed species in zeolites: methane, ethane, and propane diffusivities

Abstract: A from C3 on the ( 2 1 x 3 axis (Figure 4). The crystallographic analyses of parabanic acid and alloxan show that the C.-O-C angles corresponding to the closest intermolecular distances are 157.4 and 154.7O, re~pectively;~.~' the corresponding projected positions of the oxygens on the molecular planes of XI1 and XI11 are 1.06 A from C2 and C3 for the former and 1.19 A from C3 for the latter. Thus these oxygens, which are negative ( Figure 4), are near the most positive regions of the surface potentials, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 4 publications
2
37
0
Order By: Relevance
“…The MC simulation provides information on equilibrium properties, whereas the MD simulation also provides information on dynamic properties such as diffusivities. Numerous MD simulations have been performed on the transport of hydrocarbons in zeolites (Nicholas et al, 1993;Nowak et al, 1991;June et al, 1992;Goodbody et al, 1991). The diffusivities by MD simulations agree well with the microscopic data obtained by PFG-NMR measurement.…”
Section: Introductionsupporting
confidence: 66%
“…The MC simulation provides information on equilibrium properties, whereas the MD simulation also provides information on dynamic properties such as diffusivities. Numerous MD simulations have been performed on the transport of hydrocarbons in zeolites (Nicholas et al, 1993;Nowak et al, 1991;June et al, 1992;Goodbody et al, 1991). The diffusivities by MD simulations agree well with the microscopic data obtained by PFG-NMR measurement.…”
Section: Introductionsupporting
confidence: 66%
“…Figure 6 shows the variation of mean square displacement, ( u 2 ( t ) ) , as a function of time for various temperatures. Diffusion coefficients at various temperatures obtained from the Einstein relationf9 D = (u2(t))/2dit ( 6 ) valid for long times are listed in Table 111. Here di is the dimensionality of the system, taken as 3 in the present case.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10 shows the variation of the total energy (U) = (Ugh) + ( Ugg) with d, the perpendicular distance between the sorbate and the plane of the eight-ring window. We know that the sorbate has to pass through the eight-ring window to migrate 6 . 0 to another cage.…”
Section: Short-time Behaviormentioning
confidence: 99%
“…Often the use of a rigid lattice is based on the intuition that the dynamical behavior of fairly small guests will not be altered if a flexible framework is used. 37 In one study by Demontis et al, 38 both flexible and rigid frameworks were used to evaluate the diffusion rate of methane in silicalite. It was found that properties like diffusion constants, activation energies, and radial distribution functions were almost unaffected by framework vibrations.…”
Section: A Guest-host Interactionsmentioning
confidence: 99%